2012
DOI: 10.1901/jeab.2012.98-169
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Extinction and Relapse in Combined Stimulus Contexts

Abstract: Reinforcing an alternative response in the same context as a target response reduces the rate of occurrence but increases the persistence of that target response. Applied researchers who use such techniques to decrease the rate of a target problem behavior risk inadvertently increasing the persistence of the same problem behavior. Behavioral momentum theory asserts that the increased persistence is a function of the alternative reinforcement enhancing the Pavlovian relation between the target stimulus context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
71
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(87 citation statements)
references
References 32 publications
14
71
0
2
Order By: Relevance
“…Further, the occurrence of problem behavior was more pronounced following DRA than following baseline, showing that problem behavior was inadvertently strengthened during the DRA treatment even while it was being reduced in frequency of occurrence. These findings replicated the more basic results of Experiment 2, which was conducted with rats, and were then subsequently replicated with pigeons (Podlesnik, Bai, & Elliffe, 2012). Taken together, as discussed by Shahan and Sweeney (2011), ongoing reinforcement of alternative behavior produces cumulative behavioral persistence of both target and alternative behavior, and thus accounts for at least some maintenance failures of behavioral treatment.…”
Section: Applied Evaluations Of Behavioral Persistence Based On Bmtsupporting
confidence: 73%
See 1 more Smart Citation
“…Further, the occurrence of problem behavior was more pronounced following DRA than following baseline, showing that problem behavior was inadvertently strengthened during the DRA treatment even while it was being reduced in frequency of occurrence. These findings replicated the more basic results of Experiment 2, which was conducted with rats, and were then subsequently replicated with pigeons (Podlesnik, Bai, & Elliffe, 2012). Taken together, as discussed by Shahan and Sweeney (2011), ongoing reinforcement of alternative behavior produces cumulative behavioral persistence of both target and alternative behavior, and thus accounts for at least some maintenance failures of behavioral treatment.…”
Section: Applied Evaluations Of Behavioral Persistence Based On Bmtsupporting
confidence: 73%
“…This treatment was based on both the basic literature and applied literature that previously demonstrated this type of generalization (Berg, Wacker, Harding, Ganzer, & Barretto, 2007; Wacker et al, 2005). Overall, Mace et al was the first translational study to show how a commonly applied treatment could be altered in a practical manner to reduce the persistence of problem behavior (see also Mace & Nevin, in press), which have subsequently been supported in the basic literature (e.g., Podlesnik & Bai, 2015; Podelesnik et al, 2012; Podlesnik, Bai, & Skinner, 2016). …”
Section: Applied Evaluations Of Behavioral Persistence Based On Bmtmentioning
confidence: 98%
“…Podlesnik, Bai, and Elliffe (2012) confirmed this finding in a similar paradigm with pigeons, and also found that target behavior recurred at a substantial rate when all reinforcement was discontinued (relapse), suggesting some residual strengthening effect of alternative reinforcers on target behavior.…”
supporting
confidence: 70%
“…However, the present experiment was not designed to elucidate the contributions of stimulus-reinforcer and response-reinforcer relations to resistance to extinction and reinstatement since our study produced Rich and Lean components with different rates of responsedependent reinforcement. Previous experiments also arranging response-dependent rates of reinforcement during baseline have also shown an effect of training reinforcer rates on resistance to extinction and relapse, similar to the effect shown when reinforcement in increased in the Rich relative to the Lean component by (1) adding response-independent reinforcers to one of two otherwise equal components, or (2) arranging reinforcers contingent upon an alternative response (Rau et al, 1996;Nevin, 1974;Nevin et al, 1983;Nevin et al, 1990;Mauro & Mace, 1996;Podlesnik, Bai, & Elliffe, 2012;Podlesnik & Shahan, 2009). Thus, the present findings and those of similar experiments attest to the range of conditions in which the effect of stimulus-reinforcer relations on resistance to extinction and relapse can be tested.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, added reinforcers in the presence of one component stimulus had two separable effects: They weakened the response-reinforcer relation during baseline but strengthened the stimulus-reinforcer relation (see Nevin & Grace, 2000;Nevin & Shahan, 2011). Moreover, greater reinforcement rates produce greater resistance to disruption irrespective of whether the additional reinforcement is presented response independently, as in Podlesnik and Shahan (2009), dependent on the same response (e.g., Nevin, 1974;Nevin, Mandell, & Atak, 1983), or contingent upon a concurrently available response (e.g., Mauro & Mace, 1996;Nevin et al, 1990;Podlesnik, Bai, & Elliffe, 2012;Rau, Pickering, & McLean, 1996). These findings are generally robust and have been observed in a variety of animal species, ranging from fish to humans, as well as several response types and reinforcer manipulations (Ahearn, Clark, Gardenier, Chung, & Dube, 2003;Cohen, 1996;Grimes & Shull, 2001;Harper, 1999;Igaki & Sakagami, 2004;Mace et al, 1990;Shahan & Burke, 2004).…”
mentioning
confidence: 99%